WILLINGNESS TO PAY STUDY PADA KAWASAN KONSERVASI PERAIRAN PULAU KON KABUPATEN SERAM BAGIAN TIMUR AMBON - Sri Astuti; Anak Agung Putu Swabawa; I Ketut Suarja (Institut Pariwisata dan Bisnis Internasional, 2013)
This research is taken at the district of Gorom Island east Seram in scheme to find out willingness to pay from tourists that visiting maritime tourism in the water Kon island. This research is taken to begin January antil April 2013. Interview method, documentation, and library study are used in collecting data, the result of research will be analyzed by using mean approach that is quantitative analysis method, beside it used descriptive comparative analysis method that is qualitative analysis method.The result of the analysis, that willingness to pay per-coming is amount Rp. 51.500 and per-year for domestic tourist is amount Rp. 152.667, while for foreign tourist is amount Rp. 248.333. The payment system ought be applied at the area of water Kon island is pe-year system.